Taxonomy and distribution of chiggers (acarina: trombiculidae) in northcentral Florida - Ibrahim, Rohani; Chromroy, H. L. (Florida Entomological Society, 1979)
Chiggers from the northern and north central regions of Florida were collected and identified. Seven species were found: Eutrombicula al/reddugesi (Oudemans), Eutrombicula splendens (Ewing), Fonsecia (Parasecia) gurneyi gurneyi (Ewing), Walchia americana Ewing, Euschongastia rubra Farrell, Miyatrombicula [onesae Brennan and Leptotrombidium peromysci Vercammen-Grandjean. Three species are reported for the first time in Florida. The species, Leptotrombidium peromysci, is redescribed as this is the first report in S.E. United States. A key to all the species currently re- ported in Florida is included.